ソゼイ カイヒ ニ カンスル イチ コウサツ : パナマ ブンショ オ サンコウ ト シテ - 高田, 順三; タカダ, ジュンゾウ; TAKADA, Junzou (尚美学園大学総合政策学部総合政策学会, 2016)
国際調査報道ジャーナリスト連合(ICIJ)は、パナマの法律事務所「モサック・フォンセカ」から流出した新情報の一部を公開した。今回のパナマ文書の最初の報道は2016年4月3日になされた。この文書はオフショア金融取引文書の機密文書で、アイスランドのグンロイグソン首相を含む多数の政治家周辺・著名人・企業幹部・スポーツ選手などが、タックスヘイブン(租税回避地)を利用していることがわかった。彼らは、アンフェアだか、法を犯しているわけではない。彼らにしてみれば、それを行使することは自由で、何のやましいことがあろうかと思っている。事実それを利用することは法律違反ではないのだか、税の源泉国である彼らの母国に納税すべきところを回避したモラルは問われるのではなかろうか。そして、いまも現実に多くの企業や富裕者がタックスヘイブンの有利さを享受している。これは世界的レベルで悪用されており、今回のパナマ文書はほんの氷山の一角と言えよう。問題は、世界の税秩序を規律するシステムが壊れており、現行の一国一法主義の税制では対応できなくなっていることだ。そこで、この投げかけられたパナマ文書の問題について考えることにする。 The new data that ICIJ(The International Consortium of Investigative Journalists)is now making public represents a fraction of the Panama Papers, a trove of more than 11.5 million leaked files from the Panama-based law firm Mossack Fonseca, one of the world's top creators of hard-to-trace companies, trusts and foundations.The Panama Papers, first published April 3, is the largest release of data ever about the secret world of offshore companies. To date, the investigation has brought down the Iceland Prime Minister and spurred dozens of investigations and hundreds of stories about world politicians, celebrities, businesses, and sports figures who shelter money offshore. They are unfairly called the Panama Papers, but they say tax haven does not violate the Act. To shelter money offshore which gets right to the heart of the matter for anyone who believes in liberty–legality.Indeed, use of a tax haven is not illegal. Even if their involvement in tax havens is not illegal, world leaders can be held morally responsible for avoiding tax obligations in their countries, where they should have paid taxes in the first place. And, it is a fact that many companies and wealthy people are trying to reduce their taxes by taking advantage of the nature of tax havens, which are extremely low tax rates and high anonymity. The tax haven influences source of tax revenue–base erosion and profit shifting. That's at the global level, and that's only for one specific form of tax evasion: really illegal tax evasion. The Panama Papers leak ...